Influence of the normal stresses to direction of shear flow in the rheology of concentrated kaolin suspensions (2014)
Due to the multiple applications that kaolin has, including the ceramic industry where it is used as a slurry with high solid concentrations, its rheological behavior is quite important in mixing, agitation and pumping stages. After characterizing the kaolin by applying XRD, XRF, SEM and particle size methods, a rheological evaluation was performed in a rotational rheometer which consisted of measuring the primary normal stress difference N1 by a method that delivered good reproducibility results. With N1 data it was obtained a kind of viscosity known as dilatant viscosity which was found only for those suspensions with a volumetric concentration higher than 0.13. This dilatant viscosity depends on the shear rate and the CV, and it was modeled with the power law structure having good coefficients of determination. Finally it was found that the dilatant viscosity with a CV= 0.2 is almost five times the value of the shear viscosity, thus demonstrating that for a better understanding of the deformation stage must be taken into account the normal stresses in shear flow happening in the kaolin concentrated suspension.